Paediatric manpower: towards the 21st century. Issue 9 (September 1988) - Appleyard, W J; Jackson, A D
Abstract : The British Paediatric Association (BPA) has carried out a national survey of paediatric medical manpower in the hospital and community child health services. The results of the survey relating to England and Wales are presented and compared with Department of Health and Social Security (DHSS) manpower statistics. On the basis of the survey findings and current trends in the pattern of paediatric care paediatric manpower requirements over the next 10 years are estimated.